Estimation of Reinsurance Risk Value Using the Excess of Loss Method - Jumadil Saputra; Tika Fauzia; Sukono Sukono; Riaman Riaman (International Journal of Business, Economics, and Social Development, 2020)
As with any other business that has a risk of any incident in the future, the insurance business also needs protection against the risks that may arise in the company so that the company does not lose. Therefore, the need for anticipation in organizing any claims submitted by the insurance company to Reinsurance Company so that insurance company may assign any or all of the risks to reinsurance companies. In the method of reinsurance excess-of-loss there is a certain retention limits that allow reinsurance companies bear no claims incurred on insurance companies. The results of this study showed the average occurrence of claims and the risks that may be encountered by Reinsurance Company during the period of insurance. The magnitude of the risk assumed by the reinsurer relies on the model claims aggregation formed from individual claim size distribution models and distribution models the number of claims incurred in the period of insurance. Besides the magnitude of risk was also determined from the retention limit of insurance and reinsurance method used.